Enhanced Clearance of Pseudomonas aeruginosa by Peroxisome Proliferator-Activated Receptor Gamma - Bedi, Brahmchetna (Infect Immun, 2016)
The pathogenic profile of Pseudomonas aeruginosa is related to its ability to secrete a variety of virulence factors. Quorum sensing (QS) is a mechanism wherein small diffusible molecules, specifically acyl-homoserine lactones, are produced by P. aeruginosa to promote virulence. We show here that macrophage clearance of P. aeruginosa (PAO1) is enhanced by activation of the nuclear hormone receptor peroxisome proliferator-activated receptor gamma (PPARγ). Macrophages treated with a PPARγ agonist (pioglitazone) showed enhanced phagocytosis and bacterial killing of PAO1. It is known that PAO1 QS molecules are inactivated by PON-2. QS molecules are also known to inhibit activation of PPARγ by competitively binding PPARγ receptors. In accord with this observation, we found that infection of macrophages with PAO1 inhibited expression of PPARγ and PON-2. Mechanistically, we show that PPARγ induces macrophage paraoxonase 2 (PON-2), an enzyme that degrades QS molecules produced by P. aeruginosa. Gene silencing studies confirmed that enhanced clearance of PAO1 in macrophages by PPARγ is PON-2 dependent. Further, we show that PPARγ agonists also enhance clearance of P. aeruginosa from lungs of mice infected with PAO1. Together, these data demonstrate that P. aeruginosa impairs the ability of host cells to mount an immune response by inhibiting PPARγ through secretion of QS molecules. These studies define a novel mechanism by which PPARγ contributes to the host immunoprotective effects during bacterial infection and suggest a role for PPARγ immunotherapy for P. aeruginosa infections.